Simulation of a Wet Flue Gas Desulphurization (WFGD) plant in support of continuous grid supply of electricity and compliance to SO2 emission limits - Lekhuleni , Tsholofelo Bernice (University of the Witwatersrand, Johannesburg, 2024)
The wet flue gas desulphurization plant is susceptible to attrition and corrosion due to the corrosive nature of its operation. It is crucial to prevent plant downtime at any cost, as a plant failure in the WFGD could disrupt electricity supplies to the national grid. Plant failures can be avoided by using models to optimize plant operations and assure higher system performance. In this work, the Aspen simulation was used to forecast the following parameters for a wet flue gas desulphurization process: • Lowest limestone concentration or quality as absorber feed, • Highest volume of gas that can be treated, • Maximum sulphur content that could be treated in the absorber tower. Various reactions such as limestone dissolution, SO2 absorption and crystallization were simulated in Aspen. An equilibrium relation was established where the SO2/SO3 relationship in the absorber reaction could be used to predict the lowest concentration of limestone slurry and the highest volumetric flowrate that could be treated in the absorber. The pH drops in the absorber and the formation of gypsum (CaSO4) also supported the findings of the equilibrium relationship. The lowest limestone concentration limit is 16% compared to a design base of 31%. The maximum volumetric flowrate is in the range of 4,0-4.5 x 106 m3/h. The maximum sulphur content that could be treated is 1.6% S on a mass basis compared to a design base of 0.9%. However, the maximum sulphur was reduced to 1.41 % due to the limestone control dosing valve which can only supply 90000 kg/h instead of the maximum requirement of 94315 kg/h. The equilibrium relations, pH, and gypsum production can all be used to establish safe operating regimes for the WFGD plant.
A research report submitted in fulfillment of the requirements for the Master of Science in Engineering, In the Faculty of Engineering and the Built Environment , School of Chemical and Metallurgical Engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Wet flue gas desulphurisation; Liquid-gas ratio; Limestone reactivity; Coal quality; SDG-7: Affordable and clean energy; SDG-13: Climate action